Early Printed Music and Material Culture in Central and Western Europe (2021)
This book presents a varied and nuanced analysis of the dynamics of the printing, publication, and trade of music in the sixteenth and early seventeenth centuries across in Europe. Engaging with the theoretical turns in the humanities towards material culture, mobility studies and digital research, this book offers a wealth of new insights that will be relevant to researchers of early modern music and early print culture alike.